G466(P) Training on the recognition of the sick neonate. (25th October 2020) - MacRae, E; Kyaw, T; Thu, SM; Davidson, L
Abstract : Background: As part of the partnership with Myanmar paediatric society and the Royal College of paediatrics, work has been undertaken to improve child and neonatal mortality. Our aim was to increase vital sign monitoring; the recognition of the sick or deteriorating neonate and timely escalation of care. To achieve this objective, a training programme was devised for nursing staff to increase awareness of neonatal danger signs and when to inform the doctors of the patient's condition. Objective: To determine if the training programme for nursing staff was effective in improving their awareness of neonatal danger signs and when to inform the doctors of the patient's condition. This was determined by comparing their mean test scores before and after the programme for any statistically significant improvement. Method: The training was carried out amongst 17 nurses (paediatric, neonatal and nursing students) in two hospitals in the Ayeyarwady region (Hospital A and Hospital B). A poster was created detailing how to monitor the neonates, basic emergency management of sick neonates for the nursing staff and when to escalate concerns to a paediatric doctor. The poster incorporated a check list on how to assess a neonate for signs of deterioration under the headings: Breathing, Colour, Temperature, Activity and Feeding. This was then taught to the nurses using clinical videos and bedside teaching in the neonatal unit. The nurses were asked to complete a test assessing their knowledge before and after the teaching session. The mean scores were compared using the student t-test to determine if there was any statistically significant difference. Result: The data shows that there was a statistically significant improvement in the test scores after training in both hospitals. In Hospital A, the average test score before training was 61.3% but improved to 81.3% after training (p=0.007). In Hospital B the average test score before training was 83.3% and then 97.8% after training (p= 0.016). Conclusion: The training programme was effective in improving nursing knowledge in the recognition of the sick and deteriorating neonate as well as escalation of care.